Mutations and functional analysis of 14-3-3 stress response protein from Triticum aestivum: An evolutionary analysis through in silico structural biochemistry approach. (December 2018) - Bhattacharya, Shreya; Banerjee, Arundhati; Sah, Pragati Prasad; Mal, Chittabrata; Ray, Sujay
Graphical abstract: Highlights: Analysis of 14-3-3 protein, a stress response protein (mainly for heat, drought and salinity). Evolutionary analysis of wheat and other related species and phylogenetic tree. Domain analysis and prediction of conformational distributions. Thermodynamic energy calculations upon mutations. Correlation of the functional diversity of the protein in different species with mutations. Abstract: Wheat (Triticum aestivum), having high nutritional values is one of the staple food of most of the countries in the world. The productivity of the crop decreases drastically when it encounters various abiotic stresses, most common of which are heat, drought, flood and salinity. There is a crucial role of stress response proteins for the survival of the crops in stress conditions. So the study of wheat stress response proteins is of great importance to raise wheat production in different stress conditions. In this study, we analysed 14-3-3 protein, a stress response protein that is expressed in three major stresses, for example heat, drought and salinity and helps the plants to survive in those conditions. Effect of mutations in the 14-3-3 sequence was predicted using its domain, secondary structure and multiple sequence alignment of amino acid sequences from wheat and its related species. The functional diversity of the protein in different species was correlated with mutations, change in secondary structure and the evolutionary relatedness of the protein in different species. This is the first novel work for analysing the mutational effect on the structure and function of a stress response protein (14-3-3) from Triticum aestivum and its related species.